Navigating Uncharted Waters – The Shipping Sector’s Response to the COVID-19 Pandemic and Its Impact on The Perishable Food Supply Chains - Magdalena KLOPOTT (Communications of International Proceedings, 2020)
The global reefer trade of perishable food products (e.g. meat, vegetables) safeguards rising demand for food globally, contributing to the struggle against famine or malnutrition worldwide. Unfortunately, the COVID-19 pandemic has not spared shipping. Although the maritime sector has experienced many crises in its history, the recent global upheaval seems to be quite different, impacting the industry in two critical ways: a steep decrease in demand for shipping services, as well as by huge operational disruptions that no one was prepared for. Therefore, in the light of the current development of the coronavirus situation globally, the aim of this article is to scrutinize how shipping lines have managed disruptions caused by the pandemic and to investigate the ripple effects of measures taken by them on the perishable food supply chains (PFSC). The article starts with a glance at the global trade and maritime transport of perishable chilled or frozen food products and highlights the unique features of the PFSC, which make them significantly more vulnerable and prone to operational disruptions than other supply chains. Further on, disruptions in the maritime reefer shipping unleashed by the COVID-19 pandemic are examined as well as measures undertaken by ocean carriers in response to these disruptions. Finally, the ripple effects of these disturbances on PFSC management are scrutinized. The article reveals, that COVID-19 has placed unprecedented stress on the perishable food supply chains on a global scale and highlights certain limitations in the containerised trade of refrigerated products. First, congestion in seaports caused by measures taken after the coronavirus outbreak had detrimental effects on reefer operations, as they led to a massive shortage of electrical plug points in the ports to connect the reefer containers. Moreover, as a response to the congestion and to declining demand for shipping services, ocean carriers have restructured their service scheme by ships’ capacity management (e.g. by the cancellation of sailings). This, in turn, has had a huge repercussion on PFSC globally, resulting in an urgent need to address challenges such as enormous delays in cargo deliveries, shortage of reefer containers, and a lack of container ships’ capacity for perishable cargo. Furthermore, shippers have experienced increasing difficulties in keeping up with carrier scheduling changes, that rendered mid-term and long-term planning extremely difficult. Generally, the ripple effects of the pandemic have been more pronounced for the cold logistics of perishables than for those for dry cargo. The regrettable consequences of these disruptions are huge perishable food cargo losses and food wastage along the entire supply chain.
Keywords: Reefer Shipping; Disruption Management; Coronavirus Disruption; Perishables; Cold Supply Chains; Port Congestion; Reefer Shortage.